Charactered Education in Learning Indonesian Language in the High School: Case Study in SMAN 1 Surakarta, Indonesia - Aulia Rahmanisa; Sarwiji Suwandi; Slamet Subiyantoro (Budapest International Research and Critics University, 2018)
Character education is the focus of Indonesian education nowadays as people in Indonesia is experiencing a negative character shifting. In order to change negative character, character education should be taught to the young generation through the integration of the character education at school. This study aims to determine the ways of integrating the value of character education in the lesson plan and the process of Indonesian language learning in the high school. This study employed a case study method by implementing a qualitative approach. This research was carried out in State Senior High School (SMAN) 1 Surakarta, Indonesia. The technique of data collection comprised of observation, interviews, and documentation. The result of this study shows that SMAN 1 Surakarta infuses character education in Indonesian language learning. The character values, which are integrated to the lesson plan, are respect, discipline, care, courage, responsibility, justice, honesty, helping each other, and cooperation. In the learning process, the character values that are infused to the lesson plan had been successfully integrated except for three values, namely justice, helping each other, and cooperation. Those three values should be integrated during group discussion activities, unfortunately, group discussion activities were not carried out.